Trigeminal Neuralgia—A Comparative Analysis of Radiofrequency Electrode Lesioning Temperature at 65°C and 75°C for 60 Seconds Each - Tandon, Asheesh; Banson, Mabel; Bhaumik, Chudasama; Verma, Himanshu; Kushwaha, Prashant; Agrawal, Alok (Indian Journal of Neurosurgery, 2025)
Pain affecting the distribution of one or more of the three divisions of the trigeminal nerve defines trigeminal neuralgia (TN). Radiofrequency ablation (RFA) is one of its effective treatment modalities. The ideal RFA lesioning temperature is still under evaluation.The authors evaluate the efficacy of pain relief of RFA at 65 and 75°C, in patients with TN. Pain relief at 1 year was the study's primary outcome. Secondary outcomes: trigeminal division, complication rate, and recurrence rate.Medical records of patients with refractory TN at our center were reviewed from January 2016 to December 2023; last new case in May 2023. Excluded were the patients who were lost to follow-up or had incomplete data. Data extracted include age, gender, lesioning temperature, and the extent of pain relief. Pain relief was recorded on a visual analogue scale of 0 to 100. Recurrence was defined as the need for repeat RFA. The data were entered and analyzed with IBM SPSS Statistics (version 26).Fifty-six patients were reviewed. The mean age was 59.6 ± 11.9 years; slight female preponderance. The commonest side of TN was the right (n = 35, 62.5%). Maxillary division (V2) was the most reported (53, 94.6%); isolated in 28 (50.0%) patients. Good-to-excellent pain relief at 1 year noted in 47 (83.9%) patients. Recurrence was 16.1%. The overall complication rate was 37.5%, commonest reported was numbness. Patients receiving the 75°C RFA had better pain relief; about 60% (n = 19) patients achieved excellent pain relief.Better pain relief was observed with 75°C RFA, compared to the 65°C RFA. However, complications were higher with the 75°C RFA.
Keywords: trigeminal neuralgia; radiofrequency ablation; pain relief